2011
DOI: 10.1037/a0024613
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the perceptions and experiences of faculty who teach multicultural counseling courses: An exploratory study.

Abstract: Professional psychologists who teach multicultural counseling courses often face significant challenges, and very little information is available on their perceptions and experiences. A survey blending quantitative and qualitative questions was distributed to 169 faculty members who teach multicultural counseling courses. Results indicate that most faculty members surveyed typically incorporated selfdisclosure when teaching and viewed their cultural identity as influential in how they teach. They also identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…I tried to incorporate various exploratory ways to open the dialogue about diversity as well as each of ourselves. [My journal-2012-week 1] This is well aligned with prior studies that identified that relationship building with students is one of the core practices adopted by many teacher educators when teaching sensitive course topics across the discipline (Han et al, 2014;Kitchen, 2005;Reynolds, 2011). In fact, as a result of such positive climate and relationship building, many students felt safe to share their shortcomings or cognitive dissonances.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…I tried to incorporate various exploratory ways to open the dialogue about diversity as well as each of ourselves. [My journal-2012-week 1] This is well aligned with prior studies that identified that relationship building with students is one of the core practices adopted by many teacher educators when teaching sensitive course topics across the discipline (Han et al, 2014;Kitchen, 2005;Reynolds, 2011). In fact, as a result of such positive climate and relationship building, many students felt safe to share their shortcomings or cognitive dissonances.…”
Section: Resultssupporting
confidence: 78%
“…Firstly, when teaching diversity in higher education contexts, teacher educators have widely endorsed building relationship with students, creating a safe learning environment, and being responsive as a critically powerful tool, especially to overcome tensions with students (Dunn et al, 2014;Han et al, 2014;Kitchen, 2005;Reynolds, 2011). I too have highly valued these approaches as pivotal foundations of my instruction.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, initial awareness, depth of understanding, receptivity toward multicultural processes, degrees of engagement, and progression are variable to each student. Moreover, challenges may emerge as course content is delivered and as curriculum is developed or in response to the learning environment (Fier & Ramsey, ; Reynolds, ). Approaches to curriculum development of multicultural content may differ across various professional disciplines; however, even when standards for course content exist, instructors’ teaching methods may vary drastically.…”
Section: Challenges In Multiculturalism In Counselor Educationmentioning
confidence: 99%
“…Intergroup conflict and tension have been cited as a challenge for professors, and the need to create safe environments has been emphasized (Reynolds, ). In addition, conflict can be directed at the professor when students’ personal views are challenged in the classroom; this is an issue that is particularly faced by faculty of color (Sue et al, ).…”
Section: Types Of Conflict and Interventionsmentioning
confidence: 99%
“…Skillful use of de‐escalating and mediative strategies and interventions is necessary to ensure positive student outcomes in the critical area of multicultural development (Choudhuri, ; Sue, Torino, et al, ; Young, ). To better conceptualize the variety of response options or interventions, we identified three themes for 12 interventions from the literature: (a) de‐escalation only (Burgess & Burgess, ), (b) supportive confronting (Sue et al, ; Sue & Sue, ), and (c) protective confronting (Reynolds, ; Young, ). These interventions and strategies are used as a basis for the strategies counselor educators applied to hypothetical situations in the current research study.…”
Section: Types Of Conflict and Interventionsmentioning
confidence: 99%